Effect of retrofit interventions on seismic fragility of Italian residential masonry buildings. (1st June 2023) - Follador, Veronica; Carpanese, Pietro; Donà, Marco; da Porto, Francesca
Abstract: In this paper, the vulnerability of ordinary unreinforced masonry (URM) buildings is analyzed, and the literature related to possible seismic retrofit interventions is reviewed in order to investigate their feasibility and effectiveness. These interventions are then simulated on a database of 445 buildings through Vulnus_4.0 software, that performs simplified mechanical analyses accounting for both global and local behavior of masonry buildings. The fragility of each building is assessed both in its as-built state and after the simulation of retrofit interventions. Fragility curves are then processed, and a fragility model for four building typologies is obtained for the as-built and the seismic retrofitted configurations. Lastly, mean damage maps are elaborated, and the performance of the proposed retrofit interventions is analyzed. The results of this work allow evaluating and comparing the improvement of seismic behavior brought by various retrofit interventions and could serve as a basis for further theoretical studies and for practical design in real cases.